Pemberdayaan Ekonomi Umat Islam Indonesia Melalui Wakaf Produktif - Ahmad Syakir (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
This article discusses the importance of economic empowerment of Indonesian Muslims through waqf productive. Waqf has been understood by the public merely provides a treasure that is not productive in the form of land / soil to be used as a mosque or school by taking donations from the public, it is this which makes the stagnation of waqf in Indonesia, the waqf productive can be a solution to overcome the stagnation of the development of waqf. The Indonesian Ulema Council has ratified cash waqf, it makes people could donating his money to institutions or organizations entity endowments, other problems encountered in the development of waqf in Indonesia is on the development of management of endowment resources, it is because of the lack of level of professionalism, commitment and an understanding of cash waqf endowments were converted into productive efforts, thus the productive endowments could be the active solution in poverty alleviation and economic improvement of the people.